The Effect of ZIS-DSKL Funds and GDP on Poverty Levels in Indonesia - Surury, Nurul Azizah; Huda, Nurul; Rini, Nova; Fatwa, Nur; Wiliasih, Ranti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The study aims to analyze the influence of the distribution of Zakat, Infaq, Sedekah, and Other Religious Social Funds (ZIS-DSKL) and Gross Domestic Product (GDP) growth on the poverty rate in Indonesia for the period 2015-2022. The data used are secondary data obtained from the Central Statistics Agency and the Center for Data and Information Systems of the Indonesian Ministry of Trade. The analysis method employed is multiple regression. The analysis findings suggest a significant impact of the distribution of ZIS-DSKL funds and GDP growth on the poverty rate in Indonesia. The poverty rate in Indonesia can be decreased by increasing the distribution of ZIS-DSKL funds and promoting GDP growth, as revealed by their respective influences. It is important to raise public awareness about zakat obligations, ensure transparency in fund management, and carefully select programs aimed at alleviating poverty to enhance the effectiveness and efficiency of ZIS-DSKL fund distribution. The government needs to continue promoting inclusive and sustainable economic growth through pro-investment policies, infrastructure development, access to education and skills training, and strengthening potential economic sectors. Further research is necessary to understand the relationship between the distribution of ZIS-DSKL funds, GDP growth, and the poverty rate in Indonesia, providing deeper insights and more accurate data to formulate more effective policies to address poverty in Indonesia.